Tea Franchises in Indonesia: Between Culture, Business and Innovation (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The tea franchise industry in Indonesia has experienced significant growth over the past decade, transforming the traditional tea drinking culture into a modern business opportunity. This research explores the dynamics of tea franchises in Indonesia through cultural perspectives, business strategies, and innovation. This study aims to identify critical success factors, cultural adaptation strategies, and innovation models implemented by major tea franchise brands operating in Indonesia. Using a qualitative research method with a phenomenological approach, data was collected through in-depth interviews with 25 franchise owners, 15 brand managers, and 50 consumers in five major cities in Indonesia, complemented by observation and document analysis. The findings reveal that successful tea franchising effectively balances three key elements: maintaining Indonesia's tea drinking culture while introducing modern consumption patterns, implementing adaptive business models that accommodate local economic conditions, and continuously innovating in product development and service delivery. The study identified four key innovation patterns: product localization (85% of successful franchises), digital integration (92%), experiential marketing (78%), and sustainability practices (68%). Cultural factors significantly influence menu adaptation, store ambient design, and marketing strategy. This study concludes that tea franchising in Indonesia represents a unique hybrid business model that successfully blends the global franchise system with local cultural values, creating a sustainable competitive advantage in the beverage industry.